The Transcription Regulator Patz1 Is Essential for Neural Stem Cell Maintenance and Proliferation - Mancinelli, Sara; Vitiello, Michela; Donnini, Maria; Mantile, Francesca; Palma, Giuseppe; Luciano, Antonio; Arra, Claudio; Cerchia, Laura; Liguori, Giovanna Lucia; Fedele, Monica (Frontiers in Cell and Developmental Biology, 2021)
Proper regulation of neurogenesis, the process by which new neurons are generated from neural stem (NS) and progenitor cells (PCs), is essential for embryonic brain development and adult brain function. The transcription regulator Patz1 is expressed ubiquitously in mouse early embryo and has a key role in embryonic stem cell maintenance. At later stages, the detection of Patz1 expression mainly in the developing brain suggests a specific Patz1 involvement in neurogenesis. To address this point, we first got insights in Patz1 expression profile in different brain territories at both embryonic and postnatal stages, evidencing a decreasing temporal Patz1 expression gradient, together with its enrichment in the adulthood in the structures in which neurogenesis is still active. Then, we performed in vivo and ex vivo analysis of Patz1-knockout mice, showing a significant reduction in the number of NS/PCs, as well as of their self-renewal capability, in Patz1-null mice compared to controls in both embryos and adults. Consistently, molecular analysis revealed the downregulation of stemness markers in NS/PCs derived from Patz1-null mice. Overall, these data demonstrate the requirement of Patz1 for NS/PC maintenance and proliferation, suggesting new roles for this key transcription factor specifically in brain development and plasticity, with possible implications for neurodegenerative disorders and glial brain tumors.